2010
DOI: 10.1016/j.heares.2010.03.085
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling and Atoh1 expression during hair cell regeneration in the mouse utricle

Abstract: The mammalian vestibular epithelium has a limited capacity for spontaneous hair cell regeneration. The mechanism underlying the regeneration is not well understood. Because the Notch signaling pathway mediates the formation of the sensory epithelial mosaic patterning during ear development, it may also play a role in hair cell regeneration in the mature mammalian vestibular epithelium after a lesion. To investigate the process of spontaneous regeneration in the vestibular epithelium vis-à-vis changes in Notch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 43 publications
4
56
1
1
Order By: Relevance
“…In contrast to zebrafish, the Notch target genes are decreased only modestly, and Notch signaling is still active, in hair cell-depleted neonatal mouse cochleae and 3-to 4-wk-old mouse utricles (55,56,61). Therefore we hypothesize that the failure of transient Notch down-regulation in mammals could be one of the reasons that mammalian hair cells do not regenerate spontaneously after injury.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast to zebrafish, the Notch target genes are decreased only modestly, and Notch signaling is still active, in hair cell-depleted neonatal mouse cochleae and 3-to 4-wk-old mouse utricles (55,56,61). Therefore we hypothesize that the failure of transient Notch down-regulation in mammals could be one of the reasons that mammalian hair cells do not regenerate spontaneously after injury.…”
Section: Resultsmentioning
confidence: 92%
“…In zebrafish, Notch signaling is transiently down-regulated 1 h after hair cell death, correlating with the attenuation of sox2 and up-regulation of atoh1a. The interactions between Notch signaling, sox2, and atoh1a have not yet been tested in the zebrafish lateral line; however, because of their behavior during regeneration, it is very likely that their regulation is similar to that occuring during mouse, Xenopus, and zebrafish central nervous system or sensory organ development (23,52,61,(91)(92)(93). During murine ear development Sox2 expression depends on Notch signaling and is required for the acquisition of neural potential in the prosensory epithelium (52).…”
Section: Notch Signaling Is Down-regulated Early In Lateral Line Hairmentioning
confidence: 99%
“…These studies have shown, for example, that hair cell damage in the avian cochlea and utricle, as well as in the zebrafish lateral line, results in the upregulation of Notch target genes (Daudet et al, 2009;Ku et al, 2014;Ma et al, 2008;Stone and Rubel, 1999). Furthermore, although the regenerative capacities of the mammalian cochlea and utricle are limited, the expression of Notch target genes in both of these organs also increases after damage (Batts et al, 2009;Korrapati et al, 2013;Lin et al, 2011;Mizutari et al, 2013;Wang et al, 2010).…”
Section: Kip1mentioning
confidence: 99%
“…(1:400, Abcam); rabbit anti-HNF-3g (Foxa3) (1:100, Santa Cruz); rabbit anti-GFP (1:500, Invitrogen); rabbit anti-Hes5 (1:200, Chemicon) (Batts et al, 2009;El-Hashash et al, 2011;Li et al, 2009;Wang et al, 2010). Immunofluorescence was performed using secondary antibodies conjugated to Alexa Fluor 488 or 596 (1:200, Invitrogen) and analyzed using a Zeiss confocal laser-scanning microscope (LSM510 META) as previously described .…”
Section: Immunohistochemistrymentioning
confidence: 99%